2022
DOI: 10.1007/s10643-021-01304-z
|View full text |Cite
|
Sign up to set email alerts
|

From Full Day Learning to 30 Minutes a Day: A Descriptive Study of Early Learning During the First COVID-19 Pandemic School Shutdown in Ontario

Abstract: When the COVID-19 pandemic was declared in March 2020, the lives of families all over the world were disrupted. Many adults found themselves working from home while their children were unable to go to school. To better understand the potential impact of these educational disruptions, it is important to establish what learning looked like during the first school shutdown in the spring of 2020, particularly for the youngest learners who may feel the longest lasting impacts from this pandemic. Therefore, the purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…The gaps of this study, in conjunction with the aims of the research, are to see early childhood educators' attitudes and beliefs towards digital screen-based technologies and digital resources in virtual kindergarten, the benefits and challenges of teaching and learning in virtual kindergarten, the technologies and resources educators used in virtual kindergarten, how educators documented play-based learning virtually, and what educators require to teach kindergarten virtually. Presently, there is little or emerging research regarding the beliefs and attitudes towards virtual teaching and learning in kindergarten, the challenges and benefits of virtual kindergarten teaching and learning, the technologies and resources used in virtual kindergarten, and recommendations for kindergarten stakeholders [14], [22], doi: 10.18178/ijiet.2023. 13.1.1783 In virtual teaching and learning [14], [15], technologies [23].…”
Section: Introductionmentioning
confidence: 99%
“…The gaps of this study, in conjunction with the aims of the research, are to see early childhood educators' attitudes and beliefs towards digital screen-based technologies and digital resources in virtual kindergarten, the benefits and challenges of teaching and learning in virtual kindergarten, the technologies and resources educators used in virtual kindergarten, how educators documented play-based learning virtually, and what educators require to teach kindergarten virtually. Presently, there is little or emerging research regarding the beliefs and attitudes towards virtual teaching and learning in kindergarten, the challenges and benefits of virtual kindergarten teaching and learning, the technologies and resources used in virtual kindergarten, and recommendations for kindergarten stakeholders [14], [22], doi: 10.18178/ijiet.2023. 13.1.1783 In virtual teaching and learning [14], [15], technologies [23].…”
Section: Introductionmentioning
confidence: 99%
“…After realising Covid‐19 was not ‘just a flu’ (Van Prooijen et al, 2022), scholarly attention started to engage with its consequences on various areas of life, such as healthcare and employment, as well as focusing on children's experiences around the world. This literature developed across two major themes: the effects of Covid‐19 on children's education (Castro‐Kemp & Mahmud, 2021; Crane et al, 2021; Kim et al, 2021; Scott et al, 2021; Spadafora et al, 2022; and others); and its impacts on family dynamics (Chen et al, 2021; Harrop, 2021; Limbers & Pavlov, 2021; and others). A third line of enquiry has developed to consider the emotional and mental health issues brought about by isolation and social distancing in children and adolescents (Chen et al, 2020; Crane et al, 2021; Egan et al, 2021; He & Li, 2021; Linnavalli & Kalland, 2021; O'Keefe et al, 2021; Sabaoui et al, 2021; Tebet et al, 2021; Wang et al, 2021; and others).…”
Section: The Impacts Of Covid‐19 On Children: Where Are the African C...mentioning
confidence: 99%
“…2015). Spadafora et al (2021) reported that the majority of educators reported they found difficulty in modifying their lesson plans that would be appropriate for online delivery of the lesson. Teachers faced difficulties in language skill teaching, termed as listening, speaking, reading and writing.…”
Section: Problems In Teaching English During Covid-19 Pandemicmentioning
confidence: 99%